Event Patterns Extracted from Transverse Momentum and Rapidity Spectra of Z Bosons and Quarkonium States Produced in pp and Pb-Pb Collisions at LHC - Ya-Hui Chen; Fu-Hu Liu; Roy A. Lacey (Advances in High Energy Physics)
Transverse momentum (pT) and rapidity (y) spectra of Z bosons and quarkonium states (some charmonium cc¯ mesons such as J/ψ and ψ(2S) and some bottomonium bb¯ mesons such as Υ(1S), Υ(2S), and Υ(3S)) produced in proton-proton (pp) and lead-lead (Pb-Pb) collisions at the large hadron collider (LHC) are uniformly described by a hybrid model of two-component Erlang distribution for pT spectrum and two-component Gaussian distribution for y spectrum. The former distribution results from a multisource thermal model, and the latter one results from the revised Landau hydrodynamic model. The modelling results are in agreement with the experimental data measured in pp collisions at center-of-mass energies s=2.76 and 7 TeV and in Pb-Pb collisions at center-of-mass energy per nucleon pair sNN=2.76 TeV. Based on the parameter values extracted from pT and y spectra, the event patterns (particle scatter plots) in two-dimensional pT-y space and in three-dimensional velocity space are obtained.